1) 6×+3+2 (×-4)=7 (×+2
2) 2(2×+1)-3 (3×-5)=4×-19
3) 4(3×-5)+3 (4×-7=10×-13
4) 5(2×-1)-3×+6 (×+2)=15+9×
5) -2×+4+5 (-×+2)=-3 (2×-7)
6) 5(2×+1)-2 (3×+2)+3×=13-5×
Răspunsuri la întrebare
Răspuns de
0
Răspuns:
6x+3+2x-8=7x+14
8x-5=7x+14
8x-7x=14+5
x=19
2). 4x+2-9x+15=4x-19
-5x+17=4x-19
-5x-4x=-19-17
-9x=-36
x=4
3). 12x-20+12x-21=10x-13
24x-41=10x-13
24x-10x=-13+41
14x=28
x=2
4). 10x-5-3x+6x+12=15+9x
13x+7=15+9x
13x-9x=15-7
4x=8
x=2
5). -2x+4-5x+10=-6x+21
-7x+14=-6x+21
-7x+6x=21-14
-x=7
x=-7
6). 10x+5-6x-4+3x=13-5x
7x+1=13-5x
7x+5x=13-1
12x=12
x=1
Alte întrebări interesante
Engleza,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă